Valerian and the city of a thousand planets [videorecording (DVD)] - Besson, Luc; DeHaan, Dane, 1987-; Delevingne, Cara, 1992-; Owen, Clive; Rihanna, 1988-; Hawke, Ethan, 1970-; Mézières, J.-C. (Jean-Claude) (Lions Gate Entertainment, 2017)
In the 28th century, Valerian and Laureline are a team of special operatives charged with maintaining order throughout the human territories. Under assignment from the Minister of Defense, the two embark on a mission to the astonishing city of Alpha. A mystery is at the center of Alpha, a dark force which threatens the peaceful existence of the city.